Wage Inequality and Structure of Consumption Demand - Hori, Takeo (Journal of Income Distribution®, 2011)
We present a model in which there is a variety of consumption goods, of which high-income individuals purchase the expensive ones that low-income individuals cannot afford. Increases in the relative supply of skilled workers suggest relative increases in the number of high-income individuals in our model. Increases therefore in the relative supply of skilled workers induces changes in consumption demands, which indirectly affect both the labor demands of firms and the relative skilled wage. We show that a) if expensive goods purchased only by high-income individuals are more skilled labor intensive goods and b) if the substitution between skilled and unskilled labor is limited in the production of each good, then an exogenous increase in the relative supply of skilled workers raises the relative skilled wage.